Systematic Review : Fast Food Consumption, Sedentary Lifestyle, And Adolescent Obesity - Tasrif, Nabila; Yuliana, Yuliana; Kasmita, Kasmita (Rifa'Institute, 2026)
development in which lifestyle choices have a substantial influence on long-term health. The rising incidence of obesity among adolescents can be attributed to the increased intake of fast food, which is heavy in calories, fat, and sugar, as well as a sedentary lifestyle. Objective: The purpose of this study is to examine the association between fast food intake, sedentary behavior, and obesity in adolescents, focusing on important contributing variables and potential solutions. Method: This literature review was carried out by examining relevant studies from databases Google Scholar. Articles published over the previous decade concentrating on adolescents were considered, whereas studies that did not expressly address obesity or included adult populations were eliminated . Result and Discussion: Frequent fast food consumption is linked to high calorie intake, poor nutritional quality, and an elevated risk of metabolic diseases. Furthermore, a sedentary lifestyle, which includes excessive screen time and little physical activity, increases the risk of obesity by supporting a positive energy balance. Effective solutions include school-based nutrition instruction, family participation, and regulations that regulate fast food marketing, as well as physical activity promotion techniques . Conclusions: Fast food intake and sedentary behavior are major factors to adolescents obesity. Addressing these challenges involves a multifaceted strategy that includes dietary changes, physical activity promotion, and policy-driven initiatives to encourage healthy habits. Further study is needed to create long-term obesity prevention measures for adolescents.